DISTANCE LEARNING SYSTEM BETWEEN PUBLIC AND PRIVATE SCHOOLS DURING THE COVID-19 PANDEMIC: A COMPARATIVE STUDY - Raharyanti, Fenny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Learning is a sustainable process, not disrupted by this COVID-19 pandemic. The impact of COVID-19 on the learning process has caused injustice between regions. This is a descriptive study to compare the implementation method of online learning between public and private elementary schools in two regencies with different geographical locations. The samples were then selected by purposive sampling, of one located in the mountains area of Garut Regency (for the public elementary school), and the other one in the urban area of Bogor Regency (for the private elementary school), within a period of 3 months (from July to September 2021). This study examines several different treatments for addressing school policy. There were parental involvement, direct learning frequencies, facility sufficiency matters, as well as assistive teaching and fidelity in health protocol implementation. In conclusion, the study from the home system or online learning policy cannot be generalized for all regions.